2018
DOI: 10.1186/s12936-018-2475-2
|View full text |Cite
|
Sign up to set email alerts
|

An expanded global inventory of allelic variation in the most extremely polymorphic region of Plasmodium falciparum merozoite surface protein 1 provided by short read sequence data

Abstract: BackgroundWithin Plasmodium falciparum merozoite surface protein 1 (MSP1), the N-terminal block 2 region is a highly polymorphic target of naturally acquired antibody responses. The antigenic diversity is determined by complex repeat sequences as well as non-repeat sequences, grouping into three major allelic types that appear to be maintained within populations by natural selection. Within these major types, many distinct allelic sequences have been described in different studies, but the extent and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…When magnified to understand the extent of parasite diversity in these provinces, the msp1 MAD20 allelic family (99%) and the msp2 3D7 allelic family was predominant (97%). These results are in accordance with an earlier study from Vietnam [ 17 ]. Another longitudinal study in the region, in Myanmar between 2004 and 2006 and 2013–2015 shows changes in the msp1 and msp2 allele distribution over time [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…When magnified to understand the extent of parasite diversity in these provinces, the msp1 MAD20 allelic family (99%) and the msp2 3D7 allelic family was predominant (97%). These results are in accordance with an earlier study from Vietnam [ 17 ]. Another longitudinal study in the region, in Myanmar between 2004 and 2006 and 2013–2015 shows changes in the msp1 and msp2 allele distribution over time [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…In Vietnam, the predominant msp1 and msp2 alleles in 2012 [ 17 ] are MAD20 [ 18 ] and 3D7 [ 19 ], respectively. This study aims to determine the distribution of the Plasmodium species and subsequently the different msp1 , msp2 genotypes and to estimate the MOI in clinical isolates from malaria endemic areas in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with a previous observation of high levels of polymorphism in both Pfmsp1 (8K1-like, 14MAD20-like, 6 RO33-like) and Pfmsp2 (41 IC3D7-like, 18 FC27-like) using an amplicon deep sequencing technique in Myanmar [ 44 ]. Similar results have been also reported by Aspeling-Jones et al who identified 225 different K1-like, 123 different MAD20-like and 9 distinct RO33-like in Africa and Asia [ 45 ]. Most of these alleles were detected in the South, hyper-endemic area, 33 and 53 distinct alleles were observed for Pfmsp1 (18 K1-like, 8 MAD20-like, and 7 RO33-like) and Pfmsp2 (35 IC3D7-like and 18 FC27-like), respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The block 2 allele is mainly represented by three families, namely, K1, MAD20, and RO33 in the field isolates. These families' allelic sequences show a highly diverse and specific geographical distribution [18]. In addition, the pattern and fragment size polymorphism of the block 2 allele serve as molecular indicators, host immunity, and malaria transmission dynamics [19].…”
Section: Introductionmentioning
confidence: 99%